Redetermination of the crystal structure of 5,14-dihydro-6,17-dimethyl-8,15-diphenyldibenzo(b,i)(1,4,8,11)tetra-azacyclotetradecine, C32H28N4 - Dey, Lucky; Rabi, Saswata; Palit, Debashis; Rahman, Ismail M. M.; Tiekink, Edward R. T. *; Roy, T. G. (De Gruyter, 2023)
C32H28N4, monoclinic, P21/c (no. 14), a = 17.7218(4) Å, b = 20.7769(5) Å, c = 14.9434(3) Å, β = 113.598(3)°, V = 5042.1(2) Å3, Z = 8, Rgt(F) = 0.0519, wRref(F2) = 0.1544, T = 294 K.